Nervos: rede de discursos e práticas de cuidado na atenção básica no município de Natal/RN - Azevedo, Luciana Fernandes de Medeiros (2010)
The Primary Health Care and one of its main strategies, the Family Health Strategy (ESF), are framed as the gateway to the Public Health System (SUS). Thus, most of the incident and prevalent health problems in the population attended should be solved at this level of care, including psychological suffering, and the so-called complaint of nerves. Nerves and nervous denote a complexity that is not always well comprehended by health workers, in such a way that the care to this kind of problem is usually inadequate. In this line of thought, the general objective of this study is to analyze the network of discourses and the care to the psychological suffering, expressed as nerves, in SUS daily Primary Health Care. Besides and more specifically, it aims at identifying the principles and guidelines of the Primary Health Care in mental health; to investigate health workers positioning before psychological suffering and complaints of nerves, and also analyze different actions and practices of care carried out in different Health Units towards complaints like nerves. Institutional Ethnography was the theoreticalmethodological perspective adopted for the work. This approach seeks to understand and analyze the institutional relationships in a particular context considering sociostructural influences and power relations, as well as daily discourses and practices. Based on interviews with health professionals, informal conversations and observations in six Health Units with ESF teams from different sanitary districts in Natal/RN, it was possible to check that the index of complaint of nerves is high. The referral to psychologists and psychiatrists, as well as the prescription of psychotropic drugs appear as the most common intervention at this level of care. In general, the participants complain that they have poor specialized knowledge about the theme of mental health. They face the problem of bad work conditions and the lack of institutional support, which make actions of illnesses prevention and health promotion even more difficult. Besides, there are different ongoing practices such as meetings for hypertensive and aged people, walk, visit, round-table discussions and community therapy. However, not all of these actions are aimed at the care of psychological suffering. It is observed that the Matrix Support, which is a methodological strategy of supervision and follow up forcases of mental health, hasn t been totally implemented in the municipal system, although it is a tool that has been used by psychologists in some Health Units in the city. It was also verified that the health care practices to the problem of nerves strongly depend on the professional s commitment with the PSF guidelines and on mental health policies, in addition to continued support, when available, from other professional who works as matrix supporter